Early childhood caries in preschool children of Kosovo - a serious public health problem - Meqa Kastriot; Berisha Merita; Begzati Agim (BMC, 2010)
Abstract Background Even though it has been widely studied, early childhood caries (ECC) remains a serious public health problem, especially in countries where there is no national program of oral health assessment and no genuine primary oral health care, such as in Kosovo. The purpose of this study was to assess the prevalence of ECC and analyze caries risk factors. Methods The subjects were 1,008 preschool children, selected by stratified random cluster sampling, in the municipality of Prishtina, capital of Kosovo. Data were collected through clinical examination and interviews. Dmft data were recorded according to WHO criteria. Bacterial examination (CRT bacteria test) and plaque test of Greene-Vermillion were used. Results The mean dmft of preschool children was found to be 5.8. The prevalence of ECC was 17.36%, with a mean dmft of 11 ± 3.6. Streptococcus mutans prevalence in ECC children was 98%. A significant correlation between dmft and S mutans counts (≥105 CFU/mL saliva) was demonstrated. A correlation was also found between daily sweets consumption and dmft in children with ECC (P < 0.001). Comparing the dmft of ECC children and duration of bottle feeding showed a statistical correlation (P < 0.001). The mean plaque test was 1.52. None of the examined children had ever used fluoride. Conclusion The prevalence of ECC was high among preschool children in the municipality of Kosovo. We recommend increasing parents' knowledge of proper feeding habits and oral health practices, and increasing preschool children's accessibility to dental services.